Galaxy groups in the updated 2MRS using a graph-theory based friends-of-friends algorithm - Lambert, Trystan (Department of Astronomy, 2021)
A galaxy group catalogue for the recently-completed 2MASS Redshift Survey (2MRS, Macri et al., 2019) is presented which consists of 44572 redshifts, including 1041 new measurements for galaxies mostly located within the Zone of Avoidance. The galaxy group catalogue is generated using a novel, graph-theory based, modified version of the Friends-of-Friends algorithm. Several graph-theory examples are presented throughout this paper, and include a new method to identify substructures within groups. The results and graph-theory methods have been thoroughly interrogated against previous 2MRS group catalogues and a Theoretical Astrophysical Observatory (TAO) mock by making use of cutting-edge visualization techniques including immersive facilities, a digital planetarium, and virtual reality. This has resulted in a stable and robust catalogue with on-sky positions and line-of-sight distances within 0.5 Mpc and 2 Mpc of the group respectively. It has recovered all major groups and clusters. The final catalogue consists of 3022 groups, resulting in the most complete “whole-sky” galaxy group catalogue to date. The 3D-positions of the groups are presented, as well as their luminosity and comoving distances, observed and corrected number of members, richness metric, velocity dispersion, and estimates of R200 and M200. Three additional catalogues are provided: 2MRS galaxies found in groups, a catalogue of subgroups, and the catalogue of 687 new group candidates which had no counterparts in previous 2MRS-based analyses.